2016
DOI: 10.11591/ijere.v5i2.4535
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Religiosity and Academic Performance amongst Accounting Students

Abstract: <p>In this paper, the association between religiosity and academic performance among accounting students enrolled at the International Islamic University Malaysia (IIUM) is explored, as recent research demonstrates a positive association between religiosity and academic success. Students' religiosity was measured using proxies from an Islamic perspective, whilst their academic performances were measured using their Cumulative Grade Point Averages (CGPA). The statistical analysis revealed no significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…In this study, majority of the students had an overall moderate mean grade, like the other similar studies. [ 7 19 20 ] They also had a moderate level of religiosity. Although the Iranian community is a religious community with a long history of religiosity, it appears that religious beliefs are gradually fading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, majority of the students had an overall moderate mean grade, like the other similar studies. [ 7 19 20 ] They also had a moderate level of religiosity. Although the Iranian community is a religious community with a long history of religiosity, it appears that religious beliefs are gradually fading.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] on medical students with different religions in New Zealand, a study by Zubira et al . [ 7 ] on nonmedical students in Malaysia, and a study by Elias et al .,[ 8 ] no significant relationship was found between religious beliefs and academic achievements. Taghavinia et al .…”
Section: Introductionmentioning
confidence: 99%
“…Some religions teach on obeying God's command to strive for perfection; such is the case for the Islamic faith. Zubairu and Sakariyau (2016) conducted a study on Muslim Malaysian students to determine if their religiosity had a positive correlation to their academic performance. The idea behind this is the higher the cumulative grade point average, the higher the religiosity.…”
Section: Religionmentioning
confidence: 99%
“…Struggling to keep motivated is a challenge among students, otherwise, they would continue to distress, be poor in academic performance, or even withdraw from university. Spirituality could be one of the solutions to help students to deal with the challenges as it has been found that spiritual well-being and academic performance havea positive association [7].Moreover, the result of a study has revealed that students with a high level of religiosity possess a high level of academic performance [8].…”
Section: Problem Statementmentioning
confidence: 99%